Enhanced detection of nitrogen dioxide via combined heating and pulsed UV operation of indium oxide nano-octahedra - Gonzalez, Oriol; Roso, Sergio; Vilanova, Xavier; Llobet, Eduard (Beilstein Journal of Nanotechnology, 2016)
We report on the use of combined heating and pulsed UV light activation of indium oxide gas sensors for enhancing their performance in the detection of nitrogen dioxide in air. Indium oxide nano-octahedra were synthesized at high temperature (900 °C) via vapour-phase transport and screen-printed onto alumina transducers that comprised interdigitated electrodes and a heating resistor. Compared to the standard, constant temperature operation of the sensor, mild heating (e.g., 100 °C) together with pulsed UV light irradiation employing a commercially available, 325 nm UV diode (square, 1 min period, 15 mA drive current signal), results in an up to 80-fold enhancement in sensitivity to nitrogen dioxide. Furthermore, this combined operation method allows for making savings in power consumption that range from 35% to over 80%. These results are achieved by exploiting the dynamics of sensor response under pulsed UV light, which convey important information for the quantitative analysis of nitrogen dioxide.
Keywords: dynamic gas sensing; indium oxide; nitrogen dioxide; pulsed UV light; UV-activated metal oxide